Search for Artistic Synthesis and New Forms of Representation in the Works of Ivan Puni and Gino Severini of the Early 1920s - Muromtseva, Olga V. (Actual Problems of Theory and History of Art, 2020)
Ivan Puni, one of the closest associates of Kazimir Malevich of the early Suprematist period, took an active part in organizing Tram B and 0,10 avant-garde exhibitions. He was a propagandist of new art, an artist whose work is so varied that it can be difficult to trace a single line of development in it, separating the main from the secondary. In 1921, Puni’s stay in Berlin was marked by a triumphant exhibition at the famous Der Sturm gallery: this display is considered one of the first examples of an innovative approach to the organization of the exhibition space developed in the 20th and 21st centuries and combining the features of total installation and performance. It is in this successful creative period that Ivan Puni is engaged in rethinking not only his own activities (the eclectic display at Der Sturm gallery drew a line under his previous art practice), but also the role of avant-garde movements, the arguments about the end of the avant-garde and the‘modern moment in painting.’ In the early 1920s, similar ideas were widely spread among avant-garde artists, captured by the all-European trend of ‘return to order.’ It seems interesting to compare the ideas of Ivan Puni, expressed in the book published in 1923 in Berlin, with the reflections of another brilliant representative of Modernism, the Italian Futurist artist Gino Severini, who became one of the main ideologists of the ‘return toorder’. Severini published a theoretical work entitled From Cubism to Classicism (1921), which explained the rejection of avant-garde experiments and the essence of a new approach to the perception and creation of art. The study of the pictorial and theoretical solutions proposed by Puni and Severini in the early 1920s allows usto take a fresh look at such issues in the development of Modern art as the globalism of 20th-century art scene, the commonality of theories and practices of artists from different countries, the influence of political and socio-cultural circumstances, and the existence of avant-garde trends after the First World War.
Keywords: Iwan Puni; Jean Pougny; Gino Severini; rappel à l’ordre; modern painting; from Cubism to Classicism; Russian avant-garde artists abroad